Historical Memory And Cultural Immunity Of Society As Resources Of The Transformation Of The Culture Of Education - Vodenko, Konstantin V. (2021)
This paper problematizes the current state of historical memory and cultural immunity as a cross-development trend in the field of education, noting that sociocultural thought has focused on understanding of historical memory and cultural immunity as parallel processes, and the transformation of the culture of education is described in relation to a new information reality, which gives rise to the dehistorization of the field of education. The author of the paper believes that the adoption of social and resource methodological schemes brings hope to get the answers for the two important aspects: first, cultural space of the educational society in the analysis of the effects of the wearable information technologies, and, in this regard, the degree of influence of historical memory and cultural immunity, second, the aspect that can be described as “specific” in the educational culture of Russian society, in which the “language” of globalization is translated into the culture-historical context of national education.